Measure for measure : a musical history of science - Levenson, Thomas, 1958- (Oxford : Oxford University Press, 1997)
This is an account of how scientific thinking has developed from the discovery of the musical scale by Pythagoras to the use today in research of genetically engineered mice. Thomas Levenson traces the history of science through the creation of both scientific and musical instruments